2008
DOI: 10.1002/sia.2990
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterization of thermally evaporated cadmium sulfide thin films

Abstract: The article reports the structural and optical properties of vacuum-evaporated cadmium sulfide (CdS) films with different thicknesses at room temperature. The structural investigations performed by means of X-ray diffraction (XRD) technique have showed that all the films have the zinc-blende structure, a face-centered cubic form with lattice constants a=b=c=5.82 Å and point group F43m. Crystallite sizes calculated from Scherrer relation are in the range of 173-345 Å. So far, because the optical parameters of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…It is also well known that CdS thin films have two crystalline modifications: the hexagonal (wurtzite) phase and the cubic (zincblende) phase. Both phases have peaks around 26 • (2Â) (Derin and Kantarlı, 2009;Natalia et al, 2009). Therefore, it is very difficult to differentiate the CdS peak from the XRD pattern of CdS thin films deposited onto ITO coated PET.…”
Section: Cds Thin Filmsmentioning
confidence: 94%
“…It is also well known that CdS thin films have two crystalline modifications: the hexagonal (wurtzite) phase and the cubic (zincblende) phase. Both phases have peaks around 26 • (2Â) (Derin and Kantarlı, 2009;Natalia et al, 2009). Therefore, it is very difficult to differentiate the CdS peak from the XRD pattern of CdS thin films deposited onto ITO coated PET.…”
Section: Cds Thin Filmsmentioning
confidence: 94%
“…The last mentioned position in 2θ corresponds to the (002) crystallographic plane of the hexagonal phase of CdS. It has been reported [4,19] that CdS can display a preferential orientation in that crystallographic plane when it is deposited by chemical bath and annealed. Additionally, it is clearly observed that the full-width at half-maximum (FWHM) of the main peak increase as a function of temperature, and is associated with the increase of the crystal size in CdS films.…”
Section: Crystalline Structure and Morphological Propertiesmentioning
confidence: 99%
“…CdS is an n-type semiconductor with a typical direct band gap of 2.42 eV and appropriated optical absorption in the visible region. CdS thin films can be obtained by different techniques, such as: sputtering [2], thermal evaporation [3,4], the SILAR method [5], spray pyrolysis [6,7], and chemical bath deposition [8,9]. Chemical bath deposition (CBD) is widely used for thin film deposition, because, it is a simple, economic, large scale, and viable technique.…”
Section: Introductionmentioning
confidence: 99%
“…Theabsorptioncoefficient is found to increase afterl aser irradiationo ft he thin film.T hisi sp ossiblydue to thei ncreasei ng rain size andt he decreasei nt he numbero fd efects 11 .I ti sc learly seen from theo ptical spectra that the absorption edge is reds hifted fori rradiated filmst hiss hift indicates ad ecreaseo ft he optical band gap' E g ' Optical band gapwas calculated usingthe following relation 1,12 : )withwavelength(").…”
Section: Opticalp Ropertiesmentioning
confidence: 99%